2010
DOI: 10.1159/000313371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socioeconomic Status and Body Mass Index on Bone Age

Abstract: Background/Aims: To evaluate the relationship of socioeconomic status (SES) and body mass index (BMI) with skeletal maturation in children from Marrakech (Morocco). Methods: SES, BMI z-score and bone age (BA) were measured in a cohort of 623 children (280 boys and 343 girls, chronological age (CA) ranged from 6.6 to 18.8 years, mean 14.1 years). BA estimation was performed with the Greulich and Pyle atlas. Two social groups (privileged and unfavorable SES) were defined. A multiple linear regression analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(15 reference statements)
1
12
0
2
Order By: Relevance
“…Chaumoitre et al who did a study of the influence of BMI and socio economic status on bone age between 6 to 18years had most children between the age group of 15 years. 19 Most of the children from the obese group were from the age group of 8 to 9 years and most of the obese children were female (66.7%). Most children in the overweight children were from the age group of 8 to 9 years and were male.…”
Section: Discussionmentioning
confidence: 94%
“…Chaumoitre et al who did a study of the influence of BMI and socio economic status on bone age between 6 to 18years had most children between the age group of 15 years. 19 Most of the children from the obese group were from the age group of 8 to 9 years and most of the obese children were female (66.7%). Most children in the overweight children were from the age group of 8 to 9 years and were male.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies reported positive associations among SES and bone-related variables (i.e., bone age, whole-body BMC and BMD, and distal forearm and calcaneus BMD) in children and adolescents, after taking into account the role of confounders, such as age, sexual maturation, height, and weight [12][13][14][15]. In addition, Arabi et al [36] showed that boys and girls of higher SES tended to have higher BMD than those from a lower SES at the subtotal body (whole body minus head), lumbar spine, forearm, total hip, femoral neck, and trochanter sites.…”
Section: Discussionmentioning
confidence: 99%
“…Parental education and occupation were also included as measures of SES [12,13,[15][16][17]25]. In the present study, parental education included four categories: lower education, lower secondary education, higher secondary education, and higher education or university degree.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
See 2 more Smart Citations